2011
DOI: 10.3174/ajnr.a2667
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Correlation between the Number of Lenticulostriate Arteries and Hypertension Based on High-Resolution MR Angiography Findings

Abstract: BACKGROUND AND PURPOSE: Hypertension, one of the most important risk factors for strokes, is associated with altered arterial anatomy and function. In this study, we compared the visualization of the LSAs by 3T 3D-TOF-MRA and DSA and quantitatively examined the LSAs in patients with hypertension by using 3D-TOF-MRA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
10
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 25 publications
2
10
0
Order By: Relevance
“…A previous study reported no difference in the mean number of LSA branches in a hypertensive group older than 50 years of age compared with an age-matched nonhypertensive group. 12 Similarly, in the present study, patients and controls were 50 years of age or older, and the average number of LSA branches was not statistically related to HTN.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…A previous study reported no difference in the mean number of LSA branches in a hypertensive group older than 50 years of age compared with an age-matched nonhypertensive group. 12 Similarly, in the present study, patients and controls were 50 years of age or older, and the average number of LSA branches was not statistically related to HTN.…”
Section: Discussionsupporting
confidence: 55%
“…15 However, there are few imaging studies of the LSA, mainly owing to the required high resolution not being readily attainable by conventional imaging modalities. 9,12,14,16 Conventional angiography can provide sufficient resolution, but it is invasive and can be applied only in selected cases. Thus, a noninvasive and widely applicable imaging method to visualize the LSA branches is required.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is based on the contrast between rapidly moving arterial blood and stationary tissues that surround the vessel. To date, most MRA studies have been limited to qualitative or semi-quantitative assessments (El-Barhoun et al, 2009), partial morphometric analyses (Bullitt et al, 2009; Chen et al, 2011), small numbers of subjects (Canham and Finlay, 2004), and proprietary datasets (Nowinski et al, 2009a). A more comprehensive structural characterization of the cerebral arterial tree can be achieved by reconstructing the vascular arborization into an explicit 3D representation (Bullitt et al, 2005; Passat et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Although the lenticulostriate arteries have been studied using various neuroimaging methods [17][18][19][20] , identification of smaller BPAs, such as distal segments or branches of the AchoA and PCA, remains a challenge [21][22][23][24] .…”
Section: Introductionmentioning
confidence: 99%